2015
DOI: 10.1021/acs.jpclett.5b01965
|View full text |Cite
|
Sign up to set email alerts
|

Softening upon Adsorption in Microporous Materials: A Counterintuitive Mechanical Response

Abstract: We demonstrate here that microporous materials can exhibit softening upon adsorption of guest molecules, at low to intermediate pore loading, in parallel to the pore shrinking that is well-known in this regime. This novel and counterintuitive mechanical response was observed through molecular simulations of both model pore systems (such as slit pore) and real metal-organic frameworks. It is contrary to common belief that adsorption of guest molecules necessarily leads to stiffening due to increased density, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…The authors conclude that it is constant, i.e., it does not change during the course of adsorption, as discussed in some previous studies. 130,131 The two PSDs, from adsorption isotherm and from strain isotherm, are close. Hence, the authors conclude that the analysis of strain isotherms is a viable approach to analyze pore-size distributions of microporous carbons.…”
Section: B Characterization Of Porous Materialsmentioning
confidence: 83%
See 1 more Smart Citation
“…The authors conclude that it is constant, i.e., it does not change during the course of adsorption, as discussed in some previous studies. 130,131 The two PSDs, from adsorption isotherm and from strain isotherm, are close. Hence, the authors conclude that the analysis of strain isotherms is a viable approach to analyze pore-size distributions of microporous carbons.…”
Section: B Characterization Of Porous Materialsmentioning
confidence: 83%
“…130 A more recent MC simulation study has shown an opposite effect: decrease of the elastic modulus for a slit pore model and for a more complex model representing ELM-11 MOF upon adsorption of LJ fluid. 131 Interestingly, the elastic properties of the fluids adsorbed in nanoporous materials also change compared to the bulk fluid. This change was not only shown by Monte Carlo simulations 132 but also measured in ultrasonic experiments.…”
Section: Coupling Between Thermodynamic and Elastic Aspects Of Adsmentioning
confidence: 99%
“…While effect (i) potentially causes apparent changes of the mechanical parameters, there may also be actual changes of the stiffness of the nonporous backbone resulting from the strain of the nonporous phase or the adsorption process (see, e.g., refs (80) and (81)).…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption can modify the apparent elastic properties of the adsorbent and lead to either an apparent stiffening or an apparent softening of the adsorbent [29,30]. The apparent stiffness of the adsorbent is a function of the stiffness of the dry adsorbent and of how the adsorption isotherm depends on both the strain of the adsorbent and the chemical potential of the adsorbate [9].…”
Section: Impact Of Adsorption On Mechanical Propertiesmentioning
confidence: 99%